A PRISON IN LATE ANTIQUE CORINTH. - Larsen, Matthew D. C. (Hesperia)
This article aims to offer a secure identification of the "Boudroumi" and the Northwest Shops in the Roman Forum at ancient Corinth as a site of incarceration in the Late Antique period. The identification is made based on both prisoner graffiti from the 5th to 6th century ce inscribed on slabs and the notebooks from the Corinth Excavations in 1901, which clarify that the slabs were discovered in situ and served as floor pavement. The small finds excavated from beneath the level of the pavement are analyzed to establish a terminus post quem for the repurposing of the structures into a prison, as well as the architectural changes made. Further, the structures' reuse is contextualized within the broader history of Corinth.